2011
DOI: 10.2147/opth.s16414
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of retinal breaks observed during 23 gauge transconjunctival vitrectomy versus conventional 20 gauge surgery for proliferative diabetic retinopathy

Abstract: Background:To assess the rate and type of retinal break formation in patients undergoing 23 gauge transconjunctival vitrectomy surgery for complications of proliferative diabetic retinopathy compared with 20 gauge vitrectomy surgery. Methods: Retrospective case notes review of two consecutive series of patients who had primary pars plana vitrectomy for complications of proliferative diabetic retinopathy by a single surgeon. The control group had standard 20 gauge vitrectomy surgery whilst the second group had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 21 publications
2
30
0
5
Order By: Relevance
“…However, we did not find this difference comparing the 23g and 25g groups. Several papers have reported that significantly fewer peripheral retinal breaks are caused by cannulated 23g systems compared to the 20g [12,13,29]. Our entry site break rate was very low in both groups at 1 eye in each group as may have been expected since the cannulated sclerostomy system is identical in length in each gauge at 6 mm.…”
Section: Discussionsupporting
confidence: 56%
“…However, we did not find this difference comparing the 23g and 25g groups. Several papers have reported that significantly fewer peripheral retinal breaks are caused by cannulated 23g systems compared to the 20g [12,13,29]. Our entry site break rate was very low in both groups at 1 eye in each group as may have been expected since the cannulated sclerostomy system is identical in length in each gauge at 6 mm.…”
Section: Discussionsupporting
confidence: 56%
“…Contrary to this, Issa SA et al (2011) observed that 23-gauge transconjunctival vitrectomy surgery was associated with a lower rate of retinal break formation than 20 gauge vitrectomy for proliferative diabetic retinopathy (5 % vs 14%).…”
Section: Khanduja S Et Al Minimally Invasive Vitrectomy Surgery Inmentioning
confidence: 57%
“…PPV was found to have an intraoperative complication rate of 7.8%, with iatrogenic retinal tears by far the most frequent complication at 3%, followed by lens touch at [8][9][10][11][12] It can, however, be difficult to compare across series, as authors use different definitions of entry site break, and iatrogenic breaks. There is also a risk of publication bias, if clinicians are reluctant to report high complication rates, and the outcomes in case series of clinical interest may not be generalisable, due to their complex nature or targeted case selection.…”
Section: Resultsmentioning
confidence: 99%
“…The submacular surgery trial 13 and diabetic retinopathy vitrectomy study 14 were undertaken before the widespread introduction of wide-angle viewing systems and small-gauge surgery, which may alter the detection and occurrence of retinal breaks, respectively. 11,12 There are recent, large prospective studies of PPV for the treatment of retinal detachment, 15,16 and these reported that iatrogenic retinal breaks occur in 8-13% of cases, 16 a The value shown is the percentage of all eyes undergoing pars plana vitrectomy (PPV), despite the fact that lens touch would not occur in a pseudophakic eye. Of the 6986 eyes undergoing primary PPV, 668 had previously had cataract surgery and were therefore known to be pseudophakic, 1897 had combined PPV and cataract surgery and were therefore phakic at the time of their primary PPV, and 1238 subsequently had cataract surgery and were therefore also known to be phakic during their primary PPV.…”
Section: Resultsmentioning
confidence: 99%